2021
DOI: 10.1002/hep.31432
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: M2 Macrophage–Derived Exosomes Facilitate HCC Metastasis by Transferring αMβ2 Integrin to Tumor Cells

Abstract: Background and Aims The development and progression of hepatocellular carcinoma (HCC) is dependent on its local microenvironment. Tumor‐associated macrophages (TAMs) are deemed a key factor for the tumor microenvironment and attribute to contribute to tumor aggressiveness. However, the detailed mechanism underlying the pro‐metastatic effect of TAMs on HCC remains undefined. Approach and Results The present study proved that TAMs were enriched in HCC. TAMs were characterized by an M2‐polarized phenotype and acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(77 citation statements)
references
References 48 publications
(54 reference statements)
1
76
0
Order By: Relevance
“…2 In addition, acceleration of the migratory potential of HCC cells is induced by TAM-derived α M β 2 (CD11/18)-containing exosomes, which have been reported to activate the MMP9 signaling pathway. 200 Through the production of various cytokines, including CCL17, CCL18, and CCL22, TAMs attract Tregs to the tumor environment, thereby hampering cytotoxic T cell activation and thus promoting tumor development. 201 Mouse models of hepatocarcinogenesis and observations of human tissues have indicated that macrophage subsets in the liver have stage-dependent effects.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…2 In addition, acceleration of the migratory potential of HCC cells is induced by TAM-derived α M β 2 (CD11/18)-containing exosomes, which have been reported to activate the MMP9 signaling pathway. 200 Through the production of various cytokines, including CCL17, CCL18, and CCL22, TAMs attract Tregs to the tumor environment, thereby hampering cytotoxic T cell activation and thus promoting tumor development. 201 Mouse models of hepatocarcinogenesis and observations of human tissues have indicated that macrophage subsets in the liver have stage-dependent effects.…”
Section: Roles Of Macrophages In Resolving Inflammation During Liver mentioning
confidence: 99%
“…Many recent studies have shown that sEVs function as carriers to transport functional materials (proteins, mRNAs, microRNAs, lncRNAs) to recipient cells, and modulate recipient cell behaviour. For example, vesicular EGFR (Zhang et al., 2017), annexin A6 (ANXA6) (Keklikoglou et al., 2019) and integrin αMβ2 (Wu et al., 2020) were reported to facilitate the metastasis of recipient cells. On the other hand, several sEV cargos, were documented to suppress the cancer migration of recipient cells.…”
Section: Disscussionmentioning
confidence: 99%
“…Wu et al . recently manifested that CD11b/CD18, as well as integrin, which derived from M2 macrophage exosomes, had the potency to boost the migratory potential of HCC cells 73 . Additionally, HCC cell-derived Wnt ligands stimulate M2 polarization of TAMs, which reversely result in tumor growth, metastasis and immunosuppression in HCC 74 .…”
Section: Liver Macrophages In Pathogenesis Of Hccmentioning
confidence: 99%